Preconditioning intervention prior to allogeneic hematopoietic stem cell transplantation in patients with high-risk acute myeloid leukemia - Tachibana, Takayoshi; Izumi, Akihiko; Arai, Shota; Takeda, Takaaki; Hirose, Natsuki; Tamai, Yotaro; Sato, Shuku; Hashimoto, Chizuko; Fujimaki, Katsumichi; Ishii, Ryuji; Sakai, Hirotaka; Yamazaki, Etsuko; et al. (Experimental hematology, 2025)
•The safety and efficacy of PCIs was evaluated.•PCIs effectively and safely reduced tumor burden.•High engraftment, low relapse, and low nonrelapse mortality rates were shown.•PCI may be safe and effective with favorable survival rate. The outcomes of patients with high-risk acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (HCT) remain poor despite many attempts at developing therapeutic strategies. Preconditioning interventions (PCIs) have been applied to patients with high-risk AML to reduce the disease burden before starting the conditioning regimen. A single-center retrospective study was performed to evaluate the safety and efficacy of PCI in allograft patients with high-risk AML. Thirty-three patients with a median age of 57 (16–70) years were included to the entire cohort. Among various PCI regimens, venetoclax plus azacitidine was administered to 12 patients. The median drug withdrawal day was 0 days (range, 0–12) for low-intensity PCIs and 12 days (range, 8–14) for high-intensity PCIs. With no grade 3 nonhematological adverse events during PCIs, the median blast fraction in the bone marrow before and after PCIs decreased from 12.4% to 2.1% (p = 0.001). Excluding three patients with early complication-related deaths, all 30 patients achieved engraftment within a median of 30 days. The overall survival, cumulative incidence of relapse, and nonrelapse mortality (NRM) rates at 2 years were 67.1%, 23.9%, and 8.8%, respectively. The cumulative incidences of grade II–IV acute graft-versus-host disease (GVHD) at 100 days and chronic GVHD at 2 years were 32.4% and 23.5%, respectively. PCI may be safe and effective in promoting engraftment and reducing the risk of disease relapse without increasing the risk of NRM. Further clinical trials are warranted to establish appropriate PCI strategies.